Advances in Humanized Mouse Models to Improve Understanding of HIV-1 Pathogenesis and Immune Responses - Gillgrass, Amy; Wessels, Jocelyn M.; Yang, Jack X.; Kaushic, Charu (Frontiers in Immunology, 2021)
Although antiretroviral therapy has transformed HIV-1 from a deadly infection into a chronic disease, it does not clear the viral reservoir, leaving HIV-1 as an uncurable infection. Currently 1.2 million new HIV-1 infections occur globally annually, with little decreased over many years. Therefore, additional research is required to advance the current state of HIV management, find potential therapeutic strategies, and further understand the mechanisms of HIV pathogenesis and prevention strategies. Non-human primates (NHP) have been used extensively in HIV research and have provided critical advances within the field, but there are several issues that limit their use. Humanized mouse (hu-mouse) models, or immunodeficient mice engrafted with human immune cells and/or tissues, provide a cost-effective and practical approach to create models for HIV research. Hu-mice closely parallel multiple aspects of human HIV infection and disease progression. Here, we highlight how innovations in hu-mouse models have advanced HIV-1 research in the past decade. We discuss the effect of different background strains of mice, of modifications on the reconstitution of the immune cells, and the pros and cons of different human cells and/or tissue engraftment methods, on the ability to examine HIV-1 infection and immune response. Finally, we consider the newest advances in the hu-mouse models and their potential to advance research in emerging areas of mucosal infections, understand the role of microbiota and the complex issues in HIV-TB co-infection. These innovations in hu-mouse models hold the potential to significantly enhance mechanistic research to develop novel strategies for HIV prevention and therapeutics.